An Analysis Of Choice Consistency And Perceptual Uniformity In A Paramilitary Organization - Duncan, W. Jack; Roberts, Carter D. (Academy of Management Journal, 1972)
The primary focus of this article is upon informal relationships in a paramilitary organization. Specific attention is directed toward the sociometric identity of leadership and various other criteria of social interaction. The analysis is conducted within the broader framework of contemporary traditions of leadership research. In general, the conventional wisdom of leadership literature is confirmed, although it is expanded into the somewhat neglected field of commonweal groups.